Kinetic and mechanistic studies of base-catalyzed phenylselenoetherification of (Z)- and (E)-Hex-4-en-1-ols - Puchta, Ralph; Bugarčić, Zorica M.; et al. (Journal of Physical Chemistry A, 2012)
The mechanism of phenylselenoetherification of (Z)- and (E)-hex-4-en-1-ols using some bases (triethylamine, pyridine, quinoline, 2,2′-bipyridine) as catalysts and some solvents [tetrahydrofuran (THF) and CCl 4] as reaction media was examined through studies of kinetics of the cyclization by UV-vis spectrophotometry. It was demonstrated that the intramolecular cyclization is facilitated in the presence of bases as a result of the hydrogen bond between the base and the alkenol's OH group. The rate constants in the base-catalyzed reactions are remarkably influenced by the bulkiness and basicity of the base used and the nature of the considered nitrogen donors. The obtained values for rate constants show that the reaction with triethylamine is the fastest one. THF with higher polarity and higher basic character is better as a solvent than CCl 4. Quantum-chemical calculations [MP2(fc)/6- 311+G**//B3LYP/6-311+G** + ZPE(B3LYP/6- 311+G**] show that the cyclization of (Z)-hex-4-en-1-ol to a tetrahydrofuranoid five-membered ring is kinetically controlled, while the cyclization of (E)-hex-4-en-1-ol to the tetrahydropyranoid six-membered ring is thermodynamically controlled. This is in accordance with previous experimental findings. © 2012 American Chemical Society.
CRIS-Team Scopus Importer:2026-01-22